Relative contributions of anaemia and hypotension to myocardial infarction and renal injury: Post hoc analysis of the POISE-2 trial. Issue 5 (9th March 2023) - Turan, Alparslan; Rivas, Eva; Devereaux, P.J.; Pu, Xuan; Rodriguez-Patarroyo, Fabio A.; Yalcin, Esra Kutlu; Nault, Rod; Maheshwari, Kamal; Ruetzler, Kurt; Sessler, Daniel I.
Abstract : BACKGROUND: Hypotension and postoperative anaemia are associated with myocardial and renal injury after noncardiac surgery, but the interaction between them remains unknown. OBJECTIVES: To test the hypothesis that a double-hit of postoperative anaemia and hypotension synergistically worsens a 30-day composite of myocardial infarction (MI) and mortality and acute kidney injury (AKI). Characterising the interaction when hypotension and anaemia occur at same time on myocardial infarction and acute kidney injury. DESIGN: Post hoc analysis of the POISE-2 trial. SETTING: Patients were enrolled between July 2010 and December 2013 at 135 hospitals in 23 countries. PATIENTS: Adults at least 45 years old with known or suspected cardiovascular disease. We excluded patients without available postoperative haemoglobin measurements or hypotension duration records. Exposures were the lowest haemoglobin concentration and the average daily duration of SBP less than 90 mmHg within the first four postoperative days. MAIN OUTCOME MEASURES: The primary outcome was a collapsed composite of nonfatal MI and all-cause mortality during the initial 30 postoperative days; our secondary outcome was AKI. RESULTS: We included 7940 patients. The mean ± SD lowest postoperative haemoglobin was 10 ± 2 g dl −1, and 24% of the patients had SBP less than 90 mmHg with daily duration ranging from 0 to 15 h. Four hundred and nine (5.2%) patients had an infarction or died within 30 postoperative days, and 417 (6.4%) patients developed AKI. Lowest haemoglobin concentrations less than 11 g dl −1, and duration of SBP less than 90 mmHg was associated with greater hazard of composite outcome of nonfatal MI and all-cause mortality, as well as with AKI. However, we did not find significant multiplicative interactions between haemoglobin splines and hypotension duration on the primary composite or on AKI. CONCLUSION: Postoperative anaemia and hypotension were meaningfully associated with both our primary composite and AKI. However, lack of significant interaction suggests that the effects of hypotension and anaemia are additive rather than multiplicative. TRIAL REGISTRATION: Clinicaltrials.gov: NCT01082874.